SUMMONING NOTARIES BY PROSECUTORS AFTER THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 16/PUU-XVIII/2020 - Sri Sulistyawati; Kartina Pakpahan; Sartika Sari (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
In carrying out their duties and authorities, notaries are given legal protection as in Article 66 paragraph 1 of Law Number 2 of 2014 (UUJN). In the Constitutional Court Decision No.16/PUU-XVIII/2020, the judge rejected the lawsuit of the plaintiff PJI (Indonesian Prosecutors Association) on the basis that the plaintiff did not have legal standing. This study aims to analyze the Constitutional Court Decision No.16/PUU-XVIII/2020 regarding the examination and summoning of Notaries by the Prosecutor. This research, normative legal research, is conducted with a statute approach using the theory of authority, namely by reviewing and analyzing regulations related to the legal issues being addressed. The results show that the decision provides special protection to the duties of Notary, but also weakens the position of the Prosecutor in summoning the Notary. Article 66 of the UUJN overlaps with Article 1 paragraph (2) of the Prosecutor's Office Law which authorizes the Prosecutor as a Civil Servant with a functional position that has the specificity to carry out its duties, functions and authorities based on the law. Efforts need to be made by Prosecutors and Investigators to prevent and eradicate criminal acts involving Notaries without violating human rights and the rights of Notaries regulated by law.